2022
DOI: 10.3389/fmed.2022.979207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wu Qin Xi exercises on pain and function in people with knee osteoarthritis: A systematic review and meta-analysis

Abstract: BackgroundAs a chronic disease that affects the whole world, there is no definite treatment for knee osteoarthritis (KOA). Wu Qin Xi (WQX) is still in preliminary exploration as a traditional Chinese exercise in the treatment of osteoarthritis of the knee. The purpose of this study was to conduct a meta-analysis of previous studies and to investigate the efficacy of the WQX exercises on pain and function in patients with KOA.MethodsWe searched six databases (Pubmed, Embase, Cochrane Library, Wanfang, CQVIP, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…However, after careful reading, it was found that previous systematic reviews have included limited literature as well as indicators. In addition, for the control group, these studies 67 , 68 included studies using different intervention protocols (i.e., strength exercise, physiotherapy, health education, or drugs) or those that did not undergo any intervention. Nevertheless the intervention measures in our study control group were all conventional exercise.…”
Section: Discussionmentioning
confidence: 99%
“…However, after careful reading, it was found that previous systematic reviews have included limited literature as well as indicators. In addition, for the control group, these studies 67 , 68 included studies using different intervention protocols (i.e., strength exercise, physiotherapy, health education, or drugs) or those that did not undergo any intervention. Nevertheless the intervention measures in our study control group were all conventional exercise.…”
Section: Discussionmentioning
confidence: 99%
“…This study adhered to the following criteria for instrumental variable (IV) selection ( Wu et al, 2022 ), Each SNP was required to exhibit a significant correlation with 83 cortical and subcortical gray‐matter volumes, surpassing the genome-wide significance threshold (P < 5E-8) ( Scaturro et al, 2023 ). Evaluation of linkage disequilibrium (LD) among SNPs was conducted utilizing European sample data sourced from the 1,000 Genomes Project reference panel, wherein only the most statistically significant SNPs were retained, excluding those exhibiting an R2 value <0.001 within a clumping window of 10,000 kb ( Guo et al, 2022 ). SNPs with a minor allele frequency (MAF) of ≤0.01 were excluded to mitigate potential bias.…”
Section: Methodsmentioning
confidence: 99%
“…Knee Osteoarthritis (KOA) is a chronic degenerative disease that predominantly affects the articular cartilage of the knee joint, leading to significant pain, disability, and diminished quality of life among affected individuals ( Wu et al, 2022 ; Scaturro et al, 2023 ). As one of the most common forms of arthritis, KOA imposes a substantial burden on individuals and healthcare systems worldwide ( Guo et al, 2022 ). The global prevalence of KOA is increasing, paralleling the aging population and the rising rates of obesity, two of the principal risk factors for the development of this condition ( Du et al, 2023 ; Long et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 58 ] 4 1 4 2 2 4 4 4 3 1 4 33 A Guo et al. [ 59 ] 3 2 2 2 1 4 3 2 3 1 4 27 B Hall et al. [ 60 ] 3 4 4 3 2 4 4 3 3 2 2 34 A Heddon et al.…”
Section: Methodsmentioning
confidence: 99%